Population genetic structure of the rare species Eryngium maritimum L. (Apiaceae) in the Gulf of Gdańsk: implications for conservation and management - Minasiewicz, Julita; Borzyszkowska, Sulisława; Żółkoś, Katarzyna; Bloch-Orłowska, Joanna; Afranowicz, Renata (Biodiversity: Research and Conservation, 2012)
We examined the genetic structure and diversity of eight populations of Eryngium maritimum L. (Sea Holly) along 150 km coastline of the Gulf of Gdańsk in Poland. Allozyme electrophoresis revealed two polymorphic loci among the 31 we tested. The populations showed low levels of genetic diversity (P=6.25, A=1.062, Ht=0.026), with little genetic differentiation between populations (FST=0.03), although it was statistically significant (p<0.001). The main directions of currents and wind indicate no significant limitations to the transport of seeds between populations in the region. Therefore, the grouping of populations that are mostly congruent with their geographic locations (except HP1) might result from the low efficacy of gene flow by seeds. The significant genetic differentiation of HP1, even from close neighboring populations, might have arisen from the founder effect and barriers to the gene flow caused by anthropogenic factors such as forestation and the construction of breakwaters.